SIMULASI PERTUMBUHAN POHON DI LAHAN AGROFORESTRI SITU CISEUPAN, CISURUPAN, GARUT, JAWA BARAT MENGGUNAKAN MODEL SExI-FS - Choirul Mutaqim, Mochamad
Population growth causes more limited land for growing trees. The high dependency on forestry products has resulted in high demand of forest cultivation. However, the facts in the field show that there are still many practices of forest cultivation using monoculture system. Agroforestry is needed to overcome the problems caused by monoculture forest cultivation. At the moment, an SExI-FS model is available for simulating interactions between trees on agroforestry land in terms of the ability of a species to gain space and light. The aim of this study was to do parameterization of species in the Situ Ciseupan agroforestry land. In addition, this study also aims to compare the simulation results of cropping patterns the tree growth on Situ Ciseupan agroforestry land. This study located around the area of Situ Ciseupan, Kampung Pasir Sereh, Sirnajaya Village, Cisurupan District, Garut Regency, West Java. In this study, to obtain a more accurate parameter value, the data used are data from measurement results in the field and data from studies of literature. The data used from measurements in the field were dbh values (diameter at breast height), height, age, crown depth, canopy curve height, crown radius, CP (Crown Position), and CF (Crown Form). Meanwhile, from the results of the literature study, the data used were in the form of dbh values, maximum, height, maximum height, age, and crown width. The species measured were species that are often found in the field, namely Alnus nepalensis, Paraserianthes falcataria, Artocarpus heterophyllus, Psidium guajava, Schima wallichii, and Swietenia macrophylla. After the parameter value has been obtained, a simulation is performed using the SExI-FS model. The size of the plot is adjusted to the conditions in the land, which is 20x30m. The scenario used is a random pattern scenario, 3x3m, and 5x5m scenarios. Five individuals per tree were used in all scenarios. The results of this study were obtained by parameterizing the SExI-FS model which can simulate tree growth which is quite realistic for six species in Situ Ciseupan. In the 3x3m and 5x5m scenarios, Alnus nepalensis has a high growth compared to the other five species. Difference of cropping patterns influenced the average yield difference of dbh size in each species, indicated by the species simulated with a 5x5m cropping pattern having an average dbh size higher than the species simulated with a 3x3m cropping pattern.